PSYCHOLOGICAL AND PEDAGOGICAL MECHANISMS FOR FORMING A CULTURE OF COMMUNICATION IN ENGLISH AMONG STUDENTS (KONFERENSIYA, 2026)
In the era of globalization and digital communication, the ability of students to communicate effectively in English is no longer limited to linguistic competence alone. It requires the formation of a communication culture that integrates psychological readiness, socio-emotional intelligence, and pedagogical support. This article explores the core psychological and pedagogical mechanisms that contribute to the development of English-based communication culture among students. It highlights the role of motivation, self-confidence, emotional climate, interactive teaching strategies, and digital tools in constructing communicative competence that aligns with modern educational demands.